Pengaruh E-HRM terhadap Kepuasan dan Kinerja Karyawan pada Badan Usaha Milik Negara di Sulawesi Selatan - Amra Aeni; Edi Jusriadi; M. Hidayat (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the effect of Electronic Human Resource Management (E-HRM) on job satisfaction and employee performance and to analyze the moderating role of job satisfaction in the relationship between E-HRM and employee performance in State-Owned Enterprises (SOEs) in South Sulawesi Province. The implementation of E-HRM is expected to improve efficiency, transparency, and accessibility in human resource management, although it also faces challenges related to employee adaptation and digital readiness. This study employed a quantitative approach with a conclusive research design and a cross-sectional method. Data were collected through a structured questionnaire distributed to 100 employees of PT PLN (Persero) UP3 Makassar Selatan, PT Pelabuhan Indonesia (Persero) Makassar Branch, and PT Sinergi Gula Nusantara Takalar Sugar Factory Unit. The collected data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that E-HRM has a positive and significant effect on job satisfaction and employee performance. Job satisfaction also has a positive and significant effect on employee performance. However, job satisfaction does not moderate the relationship between E-HRM and employee performance. The study concludes that E-HRM directly enhances employee performance and should be continuously optimized to support organizational effectiveness.